b) 8 * x - 6-9 * x = 5 * x - 6
c) 2 + 4 * x - 1+2 * x = -8 + 4 * x - 7
d) -3 +7 * X - 2 = 3 * x - 11 + 6 x
e) 4 + 5 * x - 2 = 7 * x - 7
f) -8 + 7 * x + 3 = 5 x + 4 + 4x + 5

pls na teraz​



Odpowiedź :

Hanka

B)

8x - 6 - 9x = 5x - 6

8x -  9x - 5x = - 6 + 6

- 6x = 0     |:(-6)

x = 0

c)

2 + 4 x - 1+2x = - 8 + 4x - 7

4 x + 2x - 4x = - 8  - 7 - 2 +1

2x = - 16    |:2

x = - 8

d)

-3 +7x - 2 = 3x - 11 + 6x

7x -  3x - 6x = - 11 + 3+ 2

- 2x = - 6  |:(-2)

x = 3

e)

4 + 5x - 2 = 7x - 7

5x - 7 x = - 7 - 4 + 2

- 2x = - 9   |:(-2)

x = 5,5

f)

-8 + 7x + 3 = 5 x + 4 + 4x + 5

7x  - 5x - 4x =  4  + 5 + 8 - 3

- 2x = 14   |:(-2)

x = - 7